PENGARUH BRAND AWARNESS, BRAND TRUST DAN ONLINE CONSUMER REVIEW TERHADAP MINAT BELI PADA PRODUK WARDAH DI SUMBAWA - Puput Ardayanti; Lukmanul Hakim (Jurnal Nusa Manajemen, 2026)
This study aims to examine the influence of Brand Awareness, Brand Trust, and Online Consumer Reviews on Purchase Intention for Wardah products in Sumbawa. Data were collected through distributing questionnaires to respondents who were consumers or potential consumers of Wardah in Sumbawa. The study population was all potential consumers in the Sumbawa region who were interested in purchasing Wardah products, with a sample size of 150 respondents, calculated based on the guidelines of Hair et al. (2018). The data obtained were then analyzed using statistical techniques, such as multiple linear regression analysis. The results showed that Brand Awareness had a high level of awareness in the minds of consumers, Brand Trust was in the very good category, and Online Consumer Reviews had a strong influence on purchase intention for Wardah products in Sumbawa. In general, brand awareness, brand trust, and positive online consumer reviews played a significant role in growing consumer purchase intention for Wardah products.